(untitled) (Research, Society and Development, 2020)
This study introduce an analysis of male vanity and its change over time. For a long time, vanity was a concept associated with women and the feminine, while male vanity were viewed with prejudices. Nowadays, we can see men more interested with body appearance, being male care linked to well-being, self-esteem also professional and personal success. Considering only articles in Portuguese languages, from August 2012 and September 2019, a literature review was done. The aim of the research was to show the change of concepts regarding male vanity. The result obtained was that, nowadays, men take care of the body and well-being to improve self-esteem and pursue professional and personal success. Finally, the concept of male vanity is changing, since men can assume vanity without prejudice.